2016
DOI: 10.4314/jab.v99i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Tree response to bark harvest: the case of a medicinal species, <i>Garcinia lucida</i>, as source of raw materials for plant-based drug development

Abstract: Objectives: There is a huge demand for medicinal bark in developing countries and this demand is growing fast due to it high market values. To assess the effects of bark functions and tree capacities to recover from various debarking practices, a two-year experiment was conducted and several local harvest practices were tested on Garcinia lucida. Methodology and Results: For each practice, 20 healthy trees were selected and harvested. Tree health was monitored every month and the total bark regrowth was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
5
14
1
Order By: Relevance
“…The answers to these questions were compared with available ecological data derived from previous studies (Guedje et al, 2007(Guedje et al, , 2016 and field studies conducted in parallel with this survey.…”
Section: Traditional Bark Stripping Surveymentioning
confidence: 99%
“…The answers to these questions were compared with available ecological data derived from previous studies (Guedje et al, 2007(Guedje et al, , 2016 and field studies conducted in parallel with this survey.…”
Section: Traditional Bark Stripping Surveymentioning
confidence: 99%
“…The results of this study indicated that peeling off pieces of bark with a machete yielded more bark mass than hammering on the tree with a stick. Bark mass values for ring-barked trees were higher than those for partially debarked trees; however, this practice has been proved in previous study (Guedje et al, 2016) to lead to high tree mortality, rendering this practice unsuitable for bark stripping as a method of long-term bark harvesting. Another practice expecting to provide high yield of bark harvested was felling tree at 1 m above ground, something not done in this investigation.…”
Section: Discussionmentioning
confidence: 72%
“…Another practice expecting to provide high yield of bark harvested was felling tree at 1 m above ground, something not done in this investigation. However, flowering and fruiting processes, as well as productivity would completely be suppressed in that case, although the high sprouting capacity of stumps gave the tree a greater chance to reproduce in a vegetative way in natural stands and suggested that this species could be cloned (with desirable "genetic" characteristics or qualities such as the thickness of the bark) and easily brought into domestication or cultivation (Guedje et al, 2016). Bark mass obtained per G. lucida tree increases with stem diameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations